A 25-Year-Old Woman with Continues Unconsciousness For 10 Days: A Case Report and Review of Literature - Mohamad Sadegh Ghasemi; Rasoul Shajari (Case Reports in Clinical Practice)
We reported the case of a 25-year-old woman with antihistamine abuse who presented to our hospital with a GCS of 7 and no significant past medical, psychological, or allergic history. We couldn’t find any evidence of head trauma, seizures, suicide, or any other metabolic, infectious, intoxication, or electrolyte disturbances. During her 10-day admission, the patient developed non-specific manifestations such as fever, hyperthermia, agitation, hypotension, and sinus tachycardia. Physicians should always consider over-the-counter medicines such as antihistamines as a differential diagnosis for loss of consciousness in patients who do not have any footprints of intoxication in primary urine or blood tests.